Strain effects on the magnetic order of epitaxial FeRh thin films - Kumar, H. (2018)
In this work, we report the experimental results obtained on a set of ∼90 nm thick FeRh epitaxial films deposited on MgO (001), MgO (111), and Al2O3 (0001) single crystal substrates. The magnetic characterization was achieved by measuring magnetization curves and ferromagnetic resonance as a function of temperature and orientation of the films with respect to the applied magnetic field. We discuss our results by comparing the characteristics of the antiferromagnetic-ferromagnetic transition among FeRh films of the same thickness but exposed to different post-growth annealings and deposited on substrates of different crystalline orientations. We have found that there is a correlation between the strain present in the films and their magnetic behavior, observing that a change in the in-plane stress from compressive to tensile tends to shift the magnetic transition by more than 60 K. The interplay between magnetic and elastic properties was further analyzed by ferromagnetic resonance, and we have found that the magnetoelastic component of the anisotropy varies from out-of-plane to in-plane, depending on the substrate. These findings could be of great importance if a precise tuning of the magnetic transition temperature or the magnetic anisotropy is needed for a specific application.